2019
DOI: 10.1186/s12913-019-4439-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported healthcare waste segregation practice and its correlate among healthcare workers in hospitals of Southeast Ethiopia

Abstract: Background The key to the effective management of healthcare wastes is segregation of the waste at the point of generation; no matter what final strategy for treatment and disposal of wastes is selected, it is critical that waste streams are separated. In Ethiopia, healthcare waste segregation practice among healthcare workers is overlooked and scarcely addressed in the scientific literature. This hospital-based cross-sectional study was, therefore, conducted to assess healthcare waste segregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
(43 reference statements)
2
22
0
1
Order By: Relevance
“…A previous study reported that women living near waste area of hospital were more at risk from birth defects [8]. Another research also found that gender was associated with HCW segregation practice with AOR: 1.70 [9].…”
Section: Discussionmentioning
confidence: 89%
“…A previous study reported that women living near waste area of hospital were more at risk from birth defects [8]. Another research also found that gender was associated with HCW segregation practice with AOR: 1.70 [9].…”
Section: Discussionmentioning
confidence: 89%
“…Características asociadas a mayor aplicación y conocimiento en manejo de residuos fueron: edad entre 35 -44, enfermeras, matronas, personal de laboratorio, anestesiólogos y alto nivel de educación [5]. En Etiopía el 53,8% de los trabajadores de la salud reportaron buenas prácticas de segregación de residuos y se identificaron como factores asociados a ésta el tener menos de 2 años de experiencia laboral, estar informado en precauciones estándar y la presencia de contenedores separados para los diferentes residuos [6].…”
Section: Selección De Gases Y Reactivos Menos Contaminantesunclassified
“…The rising demand for PPE, sanitary products, and other sterilization products by healthcare workers and/or the general public and their improper disposal may lead to the generation of more infectious and hazardous waste, and thus should be stored in properly labeled double-lined sealed bags. Moreover, the amount of non-infectious waste ( ≥ 80% of the total healthcare waste generation) needs to be segregated, collected, and disposed of as municipal waste (Sahiledengle 2019 ). Furthermore, the food waste and the packaging materials discarded after being used by COVID-19 positive patients also contribute to the spread of disease and thus should be handled with caution.…”
Section: Adopted Recommendationsmentioning
confidence: 99%